"Obah" Business Assistance for Productivity of People With Mental Disorders (ODGJ) Through Economic Token Motivation and Online Marketing - Kusbaryanto Kusbaryanto; Asroni Asroni; Warih Andan Puspitosari (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
Decreased productivity and quality of life experienced by People with Mental Disorders (ODGJ) are caused by decreased cognitive, personal and social functions which will affect their ability to work and be productive. ODGJ lose their job and find it difficult to find a job. Omah Barokah (OBAH) is a business established to provide opportunities for ODGJ to work and be productive. OBAH has been running for 2 years and needs assistance to increase employee motivation, expand marketing and financial management. This service activity aims to improve the quality of OBAH, which is a food business located in Kembaran Hamlet, Tamantirto, Kasihan, Bantul. Participants are 8 employees and 2 managers. The service team compiled a module for improving the OBAH business. The activity was carried out for 1 month in the form of providing motivation to work through online videos for 3 meetings. Online marketing assistance through website creation. Program results are measured by increasing employee motivation and improving the quality of online marketing. The results of the training will continue to be carried out by the manager so that the OBAH business continues to grow.